2019
DOI: 10.1039/c9tb01400d
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione triggered degradation of polydopamine to facilitate controlled drug release for synergic combinational cancer treatment

Abstract: Here we report a novel mechanism for triggering drug release in the polydopamine (PDA)-coated magnetic CuCo2S4 core–shell nanostructure by glutathione (GSH) triggered degradation of PDA for release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 57 publications
1
35
0
Order By: Relevance
“…[ 34,40 ] Glutathione has also been shown to degrade polydopamine and is present in different cell types. [ 41 ] Degradability of polydopamine has been explicitly demonstrate in in vivo experiments as well. [ 39,42 ] In particular, intravenous injection of polydopamine was shown before to have an excellent safety profile.…”
Section: Introductionmentioning
confidence: 99%
“…[ 34,40 ] Glutathione has also been shown to degrade polydopamine and is present in different cell types. [ 41 ] Degradability of polydopamine has been explicitly demonstrate in in vivo experiments as well. [ 39,42 ] In particular, intravenous injection of polydopamine was shown before to have an excellent safety profile.…”
Section: Introductionmentioning
confidence: 99%
“…The degradation of melanin with a PNs-like structure has been shown to take more than 8 weeks in vivo 23 . It has been reported that PDA is degraded in the cytoplasm via the reducing catalytic activity of glutathione 25 . It has been shown that intravenous injection of PNs does not cause histological or hematological toxicity in mice 6 .…”
Section: Discussionmentioning
confidence: 99%
“…The morphologies and structures of the PEG modified exosomes were confirmed by TEM, cryo‐TEM, zeta‐potential, FTIR, and SEC. As it is possible for PDA to become permeable and disassemble in physiologically relevant environments, [14,21,22] the successful engineering of PDA and PEG‐modified exosomes provides promise for future applications.…”
Section: Figurementioning
confidence: 99%